La construction de l’ethos scientifique: stratégies d’ effacement et d’inscription de soi dans des dissertations académiques - Duarte, Isabel Margarida; Pinto, Alexandra Guedes (Redis: Revista de Estudos do Discurso, 2015)
Due to the necessity to build the ‘rhetoric of objectivity’, the scientific ethos is normally erased from the surface of the discourse. This process of erasure is obtained through a series of linguistic methods that are widely studied in research on the matter. Nonetheless, this conven- tion of the impersonal reporting, strongly pervasive as a marker of the scientific genre, generates several relevant questions for the construction of the discourse of Science, such as the question of the ‘enunciative responsibility’ (Marques, 2013). Based on the analysis of a corpus of Masters Reports in Applied Linguistics – Language Teaching - presented between 2009 and 2014 in FLUP, this work aims at discussing whereas the non-positioning of the enunciator in the masters dissertations, through the use of epistemic modalizators, is a means of building the “humble” and mitigated scientific ethos or whereas it is a means of disclaiming responsibility for the scientific construction on the part of the investigators. Also, in a discourse that is typically impersonal, the work also aims at accounting for the formal traces of the enunciator in elements of evaluative modalization.